Repositioning Vocational Education within a Tourism-Led Regional Skills Ecosystem: The Case of SMK Negeri 1 Praya after the Mandalika Circuit Development - Mila Noviana; Sumitro Sumitro; Rozy Mursyidan Anfasah (Tinta Emas Publisher, 2026)
Tourism-destination development and international events can rapidly restructure local labor demand, yet limited research explains how vocational secondary schools adapt institutionally to such place-based economic change. This study examines how SMK Negeri 1 Praya reconstructed its educational role following the expansion of the Mandalika Special Economic Zone and the Mandalika International Circuit in Lombok, Indonesia. A qualitative single-case design was employed. Evidence was generated through in-depth interviews with school leaders, productive-subject teachers, students, and relevant external stakeholders; observation of school practices; and analysis of institutional documents. The material was examined thematically through coding, category development, cross-source comparison, and theme construction, with source and method triangulation used to strengthen credibility. Four interdependent mechanisms were identified: contextualizing the curriculum toward hospitality and tourism demand; building a school-industry partnership infrastructure; extending experiential learning through internships, industry guest instructors, a teaching factory, and competency certification; and integrating technical preparation with communication, discipline, teamwork, and service ethics. The findings indicate that SMK Negeri 1 Praya has moved beyond the conventional role of instructional provider and increasingly operates as a regional skills intermediary linking learners, employers, government-related tourism actors, and neighboring vocational schools. Nevertheless, partnership volume alone does not guarantee meaningful learning, equitable access, or sustainable school-to-work transitions. The study contributes a place-sensitive account of vocational-school adaptation within a tourism-led regional skills ecosystem and highlights the need to evaluate partnership quality, graduate outcomes, and the balance between immediate occupational demand and broader, transferable vocational knowledge.